Carbon‐Coordinated Single Cr Site for Efficient Electrocatalytic N2 Fixation. Issue 6 (21st April 2021) - Song, Wei; Fu, Ling; He, Chaozheng; Xie, Kun
Abstract: Electrocatalytic nitrogen reduction reaction (NRR) is a very promising method for ammonia (NH3 ) synthesis under ambient conditions, which can provide alternative routes to the traditional Haber–Bosch process and realize green NH3 synthesis. In this study, the electrocatalytic performance of chromium (Cr) atom anchored to graphyne (Cr@GY) is systematically investigated using density functional theory (DFT) calculations. The results show that Cr@GY is an efficient NRR electrocatalyst which can activate the inert N≡N bond sufficiently. In particular, the enzymatic mechanism is considered as the most positive catalytic pathway with the limiting potential of −0.52 V. More importantly, Cr@GY can restrict a competitive hydrogen evolution reaction (HER). The electronic properties including Bader charge, the charge difference density (CDD), the partial density of states (PDOS) and the crystal orbital Hamilton population (COHP) have been analyzed in detail. In addition, the co‐doping of B and N atoms in GY is beneficial to reduce the energy barrier of the potential‐determining step (PDS) and promote the smooth progress of the NRR. This work can provide theoretical guidance for the experimental synthesis of the single‐atom catalysts (SACs) with high activity and stability. Abstract : The electrocatalytic performance of Cr@GY is investigated using DFT calculations. The enzymatic mechanism is considered as the most positive catalytic pathway with the limiting potential of −0.52 V. In addition, the study on electronic properties also shows that the high NRR activity is associated with the charge transfer, the orbital hybridization, and the bonding/antibonding orbital interactions.